Evidence on the Extent of Cosmetic Earnings and Revenues Management by Jordanian Companies - Bader, Ahmad Ahed; Saleh, Mousa Mohammad Abdullah (International Journal of Economics and Financial Issues, 2017)
This study investigates anomaly and rounds up or down in financial accounting numbers (sales, net income, and comprehensive net income) by applying Benford’s law to first and second digit numbers of (164) Jordanian firms, for period from (2000 to 2014). Furthermore, Jordanian firms classified into two groups (positive and negative net income), the first digit testing shows Jordanian companies to have inaccurate financial accounting numbers for sales accounts, regardless of their profit or loss results, and companies with positive net income have low evidence for manipulating net income, but firms with negative net incomes don’t manipulate it, and negative net income firms have evidence to manipulate comprehensive net income where positive net income firms don’t do such manipulation, for testing second digit there are no significant evidences for rounds up or down sales, net income, and comprehensive net income accounts, so effective acts to reducing cosmetic earning management are needed. Keywords: Benford’s law, cosmetic earning management, cosmetic revenues managements. JEL Classifications: L66, M41